Cognitive Processes of ESL Learners in Pragmatic Role-Play Tasks in Academic Settings - Bi, Nick Zhiwei (Frontiers in Psychology, 2021)
The purpose of the study was to investigate English second language (L2) learners’ cognitive processes involved in their task-based pragmatic performance in academic settings. This study, therefore, examined 30 English L2 learners’ cognitive processes when engaging in various role-play-based pragmatic performance, such as requesting a recommendation letter from a professor and negotiating an agreeable meeting time with classmates. The qualitative analyses of the participants’ retrospective verbal reports (RVRs) data indicated that the learners employed a series of cognitive, metacognitive, and pragmatic strategies when accomplishing various speech acts (e.g., requests, refusals). This study hopes to make two new contributions to the field. First, the study provides the empirical evidence to validate the theoretical taxonomy of learners’ strategy use in L2 pragmatics. Additionally, the theoretical foundations of current research on cognitive processes are primarily informed by pragmatic theories. The study, thus, aims to explicate a more comprehensive view of L2 learners’ cognitive processes in pragmatic performance by employing the theories from both pragmatic and learner strategy perspectives.